2018
DOI: 10.1080/2162402x.2018.1457600
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immune checkpoint inhibitors in non-small cell lung cancer

Abstract: Immune checkpoint inhibitors (ICIs) are new therapeutic strategies for non-small cell lung cancer (NSCLC). We aimed to quantitatively evaluate the efficacy and safety of ICIs in NSCLC. Pubmed, Embase, Cochrane Library, and Web of Science were searched for randomized clinical trials comparing ICIs with control therapies in NSCLC. Data were pooled according to Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. A total of 12 trails comprising 6,919 NSCLC patients were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
1
24
0
1
Order By: Relevance
“…Moreover, their data were obtained from indirect comparisons, and they only included EGFR-TKIs as control therapy. Wang et al 7 demonstrated that ICIs are effective in patients with NSCLC, but this meta-analysis failed to compare different tumour subtypes and focused on anti-PD-1/PD-L1 and anti-CTLA-4 inhibitors concurrently.Here, we performed a systematic review and meta-analysis to compare the clinical efficacy and immune-related AEs of anti-PD-1/PD-L1 inhibitors to optimise the management of advanced or metastatic cancer. Furthermore, we also focused on the association between anti-PD-1/PD-L1 inhibitors and potential subgroup differences, such as ICI monotherapy or ICI-based combined therapy, multiple types of regimens combined with anti-PD-1/PD-L1 inhibitors, and potential biomarkers of immune checkpoint blockade therapy.…”
mentioning
confidence: 99%
“…Moreover, their data were obtained from indirect comparisons, and they only included EGFR-TKIs as control therapy. Wang et al 7 demonstrated that ICIs are effective in patients with NSCLC, but this meta-analysis failed to compare different tumour subtypes and focused on anti-PD-1/PD-L1 and anti-CTLA-4 inhibitors concurrently.Here, we performed a systematic review and meta-analysis to compare the clinical efficacy and immune-related AEs of anti-PD-1/PD-L1 inhibitors to optimise the management of advanced or metastatic cancer. Furthermore, we also focused on the association between anti-PD-1/PD-L1 inhibitors and potential subgroup differences, such as ICI monotherapy or ICI-based combined therapy, multiple types of regimens combined with anti-PD-1/PD-L1 inhibitors, and potential biomarkers of immune checkpoint blockade therapy.…”
mentioning
confidence: 99%
“…One possible explanation is that their mechanisms are different. CTLA‐4 is mainly expressed on T lymphocytes and PD‐1/ PD‐L1 is pervasively expressed on B cells, T cells, myeloid cells, and non‐lymphoid organs . The CTLA‐4 inhibitors can reactivate suppressed T lymphocytes and trigger anti‐tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…CTLA-4 is mainly expressed on T lymphocytes and PD-1/ PD-L1 is pervasively expressed on B cells, T cells, myeloid cells, and non-lymphoid organs. 36,37 The CTLA-4 inhibitors can reactivate suppressed T lymphocytes and trigger anti-tumor response. PD-1/ PD-L1 inhibitors can lead to peripheral T-cell proliferation and infiltration into the tumor, inducing an objective anti-tumor response.…”
mentioning
confidence: 99%
“…Several prospective studies have demonstrated that both ICIs monotherapy and combination regimens showed encouraging efficacies in the treatment of NSCLC . An early meta‐analysis conducted by Wang et al provided clinical evidence that either ICI monotherapy or in combination with chemotherapy improved survival in patients with advanced NSCLC, and ICI group had fewer adverse events (AEs) . However, the meta‐analysis included all lines of treatment, and was not focused on the first‐line treatment.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 An early meta-analysis conducted by Wang et al provided clinical evidence that either ICI monotherapy or in combination with chemotherapy improved survival in patients with advanced NSCLC, and ICI group had fewer adverse events (AEs). 13 However, the meta-analysis included all lines of treatment, and was not focused on the first-line treatment. In addition, several recent randomized controlled trials (RCTs) have reported the latest results and showed more evidence of immunotherapy for the first-line treatment of NSCLC.…”
Section: Introductionmentioning
confidence: 99%